Unilateral optic neuritis as a presentation of neurobrucellosis - Rita Marques; Cristina Martins; Inês Machado; José Paulo Monteiro; Nuno Campos; Paulo Calhau (MDPI AG, 2011)
Neurobrucellosis manifesting as optic neuritis is a rare disease in childhood. We report a case of neurobrucellosis in a 11 year old girl leading to visual impairment and headache. Physical examination revealed mild oedema of right tibiotarsic joint and optic neuritis. Investigations showed CSF pleocytosis and a Brucella serum agglutination titer of 1/640. Complete reversal of the symptoms was observed after appropriate antibiotic treatment. To our knowledge only four cases of neurobrucellosis manifesting with visual impairment in childhood are previously reported in literature.